2013
DOI: 10.1186/1472-6963-13-536
|View full text |Cite
|
Sign up to set email alerts
|

Patterns, determinants and barriers of health and social service utilization among young urban crack users in Brazil

Abstract: BackgroundCrack use is prevalent across the Americas, and specifically among marginalized urban street drug users in Brazil. Crack users commonly feature multiple physical and mental health problems, while low rates of and distinct barriers to help service use have been observed in these populations. This study examined profiles and determinants of social and health service utilization, and unmet service needs, in a two-city sample of young (18–24 years), marginalized crack users in Brazil.MethodsN = 160 study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 80 publications
0
19
0
2
Order By: Relevance
“…Additionally, the difference between the prevalence of HCV exposure found in this study compared with the study conducted in the same region by Pompilio et al (2011) may be explained by the decline in the frequency of injection drug users (10.6% to 1%) [16]. In fact, in recent years, the pattern of drug use in Brazil has changed, resulting in a smaller proportion of IDU which was largely replaced by smoked or inhaled crack cocaine [1820]. …”
Section: Discussionmentioning
confidence: 66%
“…Additionally, the difference between the prevalence of HCV exposure found in this study compared with the study conducted in the same region by Pompilio et al (2011) may be explained by the decline in the frequency of injection drug users (10.6% to 1%) [16]. In fact, in recent years, the pattern of drug use in Brazil has changed, resulting in a smaller proportion of IDU which was largely replaced by smoked or inhaled crack cocaine [1820]. …”
Section: Discussionmentioning
confidence: 66%
“…Reducing stigmatizing and moralizing discourse related to drug users, especially among health and law enforcement personnel, may help encourage users to seek care before their dependence worsens and they become involved in crime. A stronger political commitment is needed to confront the drug issue in Brazil as a public health problem, with the aim of ensuring availability, stability of funds, the implementation of large-scale interventions, the training of outreach workers, and proper evaluations (Domanico and Malta 2012;Krawczyk, Filho, and Bastos 2015;Santos Cruz et al 2013b). …”
Section: Discussionmentioning
confidence: 99%
“…Considering that sex workers may have a history of homelessness, mental health issues, face discrimination, poverty, lack of access to health care and social services, incarceration, drug use, high-risk multiple male partners, and the lack of data and understanding around sex workers creates a significant barrier to HIV-prevention efforts and other complementary services (Bobashev et al 2009; Centers for Disease Control and Prevention [CDC] 2015). These factors contribute to the barriers of the client group to receiving HIVprevention activities (Santos Cruz et al 2013b). The proper treatment of alcohol and other drug users, STIs prevention, and effective strategies against crime and violence have been fundamental in the relationship between the treatment of substance dependence and broader issues of health and safety for the general population (Bobashev et al 2009;CDC 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In South America, cocaine is the drug of choice. Studies have shown young adult crack cocaine users have health and economic marginalization, an elevated risk for HIV infection and compromised health along with poor health services utilization (62)(63)(64). In the Dominican Republic, a recent study has addressed alcohol use in young adults in the context of risk for HIV infection (65).…”
Section: Linking Young Adults Substance Use/substance Use Disorders mentioning
confidence: 99%